Apocrine Adenoma of the External Auditory Canal with Pseudoepitheliomatous Hyperplasia - Ohki, Masafumi (Case Rep Otolaryngol, 2019)
The tumors derived of the ceruminous gland in the external auditory canal are rare. Here, we report a case of a ceruminous adenoma (apocrine adenoma) with refractory chronic inflammation in the external auditory canal. A 46-year-old man presented with otorrhea, itching, and a foreign body sensation in his right ear. A soft reddish protruding lesion was revealed at the posterosuperior portion of the entry to the right external auditory canal by otoscopy. The skin lesion was endaurally resected; histopathology showed luminal structures in the middle to deep layer of the epidermis and inflammatory granulation below pseudoepitheliomatous hyperplasia. The walls of the luminal structures consisted of inner luminal secretory cells featuring apical decapitation secretion and outer myoepithelial cells. The patient was diagnosed with an apocrine adenoma. Three years after surgery, there has been no evidence of recurrence. Complete resection, including the deep layer of the epidermis, is necessary.